La atribución de fuentes en la escritura académica de alumnos de grado : relevamiento de estrategias - Pasquini, Marina Haydée (2018)
Academic writing has its own conventions and patterns which make it different from other types of writing. Composing academic essays and papers poses difficulties to students who need specific instruction to acquire the rules on which different academic discourses are built. Every discipline has its own mechanisms that imply specific discourse strategies that function as models. According to Swales (1990) academic writing implies knowledge of the discipline’s conventions. These conventions and discourse strategies will be present in the students’ texts as essential elements in their future professional writing demands and should be acquired during their undergraduate years. This work explores key attribution strategies required in advanced EFL university student compositions and analyzes to what extent a group of learners at the National University of Córdoba (UNC) in Argentina use them in writing their own texts and to what degree they acknowledge and incorporate secondary sources in their works. The students were asked to write an assignment in class, as part of the requirements for the Language V writing project. Four basic linguistic resources of secondary source use were analyzed – citation, paraphrasing, quotation format, and the use of reporting verbs. The findings offer insights into student practices and suggest the need for greater and continuous pedagogical support to enable students to achieve competence in secondary source use.